2019
DOI: 10.3390/en12030521
|View full text |Cite
|
Sign up to set email alerts
|

Investigation on Oxidation Behavior of Super304H and HR3C Steel in High Temperature Steam from a 1000 MW Ultra-Supercritical Coal-Fired Boiler

Abstract: Oxidation behavior of Super304H and HR3C steel in high temperature steam from an ultra-supercritical coal-fired boiler was investigated in this paper. The results showed that the steam oxidized surface of Super304H ware composed of Fe2O3, Cr2O3 and FeCr2O4, the oxide scale had a thickness of 50–70 μm. In addition, the steam oxidized surface of HR3C ware composed of Fe2O3, the oxide scale was about 20μm in thickness and contained few pitting. The oxidation product layer of the two samples could be divided into … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 27 publications
(30 reference statements)
0
4
0
Order By: Relevance
“…[3,23,24] However, at lower exposure temperatures of 550-600°C, the oxides formed on the HR3C austenitic steel were mainly composed of (Fe,Cr) 3 O 4 spinel, Fe 3 O 4 magnetite and Fe 2 O 3 hematite, and Cr 2 O 3 was not observed at the oxide/metal interface. [25][26][27] These previous results clearly indicated that exposure temperatures have an important effect on the corrosion behavior of HR3C austenitic stainless steel in supercritical water environments.…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…[3,23,24] However, at lower exposure temperatures of 550-600°C, the oxides formed on the HR3C austenitic steel were mainly composed of (Fe,Cr) 3 O 4 spinel, Fe 3 O 4 magnetite and Fe 2 O 3 hematite, and Cr 2 O 3 was not observed at the oxide/metal interface. [25][26][27] These previous results clearly indicated that exposure temperatures have an important effect on the corrosion behavior of HR3C austenitic stainless steel in supercritical water environments.…”
Section: Introductionmentioning
confidence: 92%
“…At present, some published works have reported the corrosion behavior of HR3C austenitic stainless steel in high-temperature supercritical water. [3,[22][23][24][25][26][27] Chen et al [22] investigated the internal and external oxidation behavior of HR3C austenitic steel in a supercritical water environment at 600°C/25 MPa, and found that a thinner protective Cr 2 O 3 layer was generated at the oxide/metal interface, which could protect the sublayer matrix from further oxidation. In other reports, the oxidation characteristics of HR3C austenitic steel were analyzed in detail after being exposed in supercritical water at 600-700°C/25 MPa, a doublelayer structure with outer Fe-rich oxide layer and inner Cr-rich oxide layer was developed on HR3C austenitic stainless steel, and Cr 2 O 3 healing layer was also detected at these oxidation conditions.…”
Section: Introductionmentioning
confidence: 99%
“…The high-temperature oxidation behavior of metals is influenced by many factors, such as the oxidation temperature and the atmosphere [6,24], surface treatment [25][26][27], and grain size [28]. Fujikawa et al [29] reported that steel with a coarse grain tends to peel off easily during the cooling process at 850 • C. Li et al [30] found a spalling oxidation layer on Super304H formed under steam at 605 • C due to the difference in the internal and external expansion coefficients, with oxidation products consisting of an inner layer of chromium oxide and an outer layer of iron oxide. Zielinski et al [29] revealed that oxide layers differ completely with components and properties between HR3C and HR6W at high temperatures.…”
Section: Introductionmentioning
confidence: 99%
“…[6][7][8][9] Considerable effort has been devoted to analyze the formation of oxide scale on FeCr alloys. [1,[10][11][12] Zhu et al [1] investigated the oxidation behavior of a ferritic-martensitic steel exposed to deaerated SCW at 560-650°C and 25 MPa by oxidation experiment, and the oxidation kinetics at different temperature was analyzed. Shen et al [13] conducted a detailed characterization of material microstructure formed on stainless steels.…”
Section: Introductionmentioning
confidence: 99%